2022
DOI: 10.1155/2022/8438131
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Value of Three-Dimensional Transvaginal Ultrasound in Diagnosis of Endometrial Receptivity and Ovarian Function in Patients with Infertility

Abstract: Objective. A case-control study was conducted to explore the clinical value of three-dimensional transvaginal ultrasound in the diagnosis of endometrial receptivity (ER) and ovarian function in patients with infertility. Methods. A total of 308 infertile women treated in our hospital from March 2020 to June 2021 were enrolled as the observation group, and another 300 women of childbearing age who underwent physical examination in the same period were enrolled as the control group. The clinical value of three-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…Al-Rab et al ( 16 ) found no correlation between FSH and either FI or VI in PCOS patients. Outside this meta-analysis, Wu et al ( 43 ) found strong negative correlations between FSH and ovarian volume, antral follicle count, peak flow velocity and end-diastolic peak velocity in infertile women. We found fewer studies to report the correlations between AMH and Doppler ultrasonography measures.…”
Section: Discussionmentioning
confidence: 87%
“…Al-Rab et al ( 16 ) found no correlation between FSH and either FI or VI in PCOS patients. Outside this meta-analysis, Wu et al ( 43 ) found strong negative correlations between FSH and ovarian volume, antral follicle count, peak flow velocity and end-diastolic peak velocity in infertile women. We found fewer studies to report the correlations between AMH and Doppler ultrasonography measures.…”
Section: Discussionmentioning
confidence: 87%
“…This study investigated the application value of 3D-TVS in the assessment of DOR and POF, with the results of sex hormone detection as the gold standard, the specificity, sensitivity and accuracy of 3D-TVS in the diagnosis of DOR were 80.00%, 90.00% and 88.00% respectively; The specificity of POF was 87.50%, the sensitivity and accuracy were 95.83% and 93.75% respectively. Wu J et al 9 showed through a case-control study (308 cases vs 300 cases) that transvaginal ultrasound is of great value in evaluating ovarian reserve function and predicting ovulation, with specificity higher than 90.00% and sensitivity higher than 80.00% for AFC and OV. This is consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 In the past, the hormone level was mainly detected by biochemical examination in the evaluation of ovarian reserve function, but the biochemical examination had certain limitations and could not obtain the morphological information of the ovary. 9,11 Vaginal ultrasound is the best way to monitor follicles and the most accurate method at present. 9 Through the use of post-processing software, list marking processing can be implemented for different follicle diameters and volumes, which is convenient for clinicians to observe the subtle follicular structural changes and improves analysis of sinus follicle development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations